DX+HY=

Simple and best practice solution for DX+HY= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for DX+HY= equation:


Simplifying
DX + HY = 0

Solving
DX + HY = 0

Solving for variable 'D'.

Move all terms containing D to the left, all other terms to the right.

Add '-1HY' to each side of the equation.
DX + HY + -1HY = 0 + -1HY

Combine like terms: HY + -1HY = 0
DX + 0 = 0 + -1HY
DX = 0 + -1HY
Remove the zero:
DX = -1HY

Divide each side by 'X'.
D = -1HX-1Y

Simplifying
D = -1HX-1Y

See similar equations:

| 293+6y=500 | | 0.75x+1.5=6x+72 | | 2ln(x-5)=54 | | 7.5(-3.1w-6)+7= | | 7(x+10)=210 | | -6/5y=42 | | 7a=12 | | 10x+4=p | | 25x^2-10=2 | | ax-b=cx-7 | | 2b^2-9b+9= | | 7(x+5)=6(x-6)+x | | 3x-5=-6x+14 | | 3x-5=-6+14 | | 6y+9+9y= | | 9f+9f=2 | | 4.5(7.6z+3)-3= | | lnx+x=5 | | 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 | | 8x+10y=170 | | 0.18(2x)=59 | | y-15x=3 | | -17.3-m=22.8 |

Equations solver categories